BrachyView, A novel inbody imaging system for HDR prostate brachytherapy: Design and Monte Carlo feasibility study. Issue 7 (17th June 2013) - Safavi‐Naeini, M.; Han, Z.; Cutajar, D.; Guatelli, S.; Petasecca, M.; Lerch, M. L. F.; Franklin, D. R.; Jakubek, J.; Pospisil, S.; Bucci, J.; Zaider, M.; Rosenfeld, A. B.
Abstract : Purpose: : High dose rate (HDR) brachytherapy is a form of radiation therapy for treating prostate cancer whereby a high activity radiation source is moved between predefined positions inside applicators inserted within the treatment volume. Accurate positioning of the source is essential in delivering the desired dose to the target area while avoiding radiation injury to the surrounding tissue. In this paper, HDR BrachyView, a novel inbody dosimetric imaging system for real time monitoring and verification of the radioactive seed position in HDR prostate brachytherapy treatment is introduced. The current prototype consists of a 15 × 60 mm 2 silicon pixel detector with a multipinhole tungsten collimator placed 6.5 mm above the detector. Seven identical pinholes allow full imaging coverage of the entire treatment volume. The combined pinhole and pixel sensor arrangement is geometrically designed to be able to resolve the three‐dimensional location of the source. The probe may be rotated to keep the whole prostate within the transverse plane. The purpose of this paper is to demonstrate the efficacy of the design through computer simulation, and to estimate the accuracy in resolving the source position (in detector plane and in 3D space) as part of the feasibility study for the BrachyView project. Methods: : Monte Carlo simulations were performed using the GEANT4 radiation transport model, with a 192 Ir source placed in different locations within a prostate phantom. A geometrically accurate model of the detector and collimator were constructed. Simulations were conducted with a single pinhole to evaluate the pinhole design and the signal to background ratio obtained. Second, a pair of adjacent pinholes were simulated to evaluate the error in calculated source location. Results: : Simulation results show that accurate determination of the true source position is easily obtainable within the typical one second source dwell time. The maximum error in the estimated projection position was found to be 0.95 mm in the imaging (detector) plane, resulting in a maximum source positioning estimation error of 1.48 mm. Conclusions: : HDR BrachyView is a feasible design for real‐time source tracking in HDR prostate brachytherapy. It is capable of resolving the source position within a subsecond dwell time. In combination with anatomical information obtained from transrectal ultrasound imaging, HDR BrachyView adds a significant quality assurance capability to HDR brachytherapy treatment systems.